“Climate change” vs. “global warming”: A corpus-assisted discourse analysis of two popular terms in The New York Times - Liu, Ming; Huang, Jingyi (Journal of world languages, 2022)
“Climate change” and “global warming” are two popular terms that may be often used interchangeably in news media. This study proposes to give a corpus-assisted discourse study of the representations of climate change and global warming in (2000–2019) in order to examine how they are actually used in the newspaper. The findings show both similarities and differences in their representations in terms of the associated topics/themes, the particular ways of framing, and the perspectivization strategy employed. It is argued that a corpus-assisted discourse study of a large sample of news articles presents a more accurate picture of the actual use of the two terms in news media.